(untitled) (gjstudies, 2019)
This research examines the intricate relationship between audit quality, information systems governance maturity, and fraud risk management effectiveness incommercial banking institutions. Through empirical analysis of 127 commercialbanks operating in the United States from 2015 to 2018, this study develops acomprehensive framework that quantifies the impact of IT governance structureson fraud risk exposure. The research employs a mixed-methods approach, combining quantitative analysis of regulatory filings, audit reports, and fraud incidentdata with qualitative assessment of governance practices. Results demonstrate thatbanks with mature IT governance frameworks experience 47% lower fraud-relatedlosses compared to institutions with underdeveloped governance structures. Thestudy introduces a novel Integrated Governance-Audit Quality (IGAQ) index thatsignificantly predicts fraud risk reduction. Findings reveal that audit committeeexpertise in information technology and robust cybersecurity oversight mechanismsare critical determinants of fraud prevention effectiveness. The research contributesto both academic literature and practical implementations by providing evidencebased guidelines for enhancing audit quality through improved information systemsgovernance in the banking sector.